1983
DOI: 10.1073/pnas.80.23.7055
|View full text |Cite
|
Sign up to set email alerts
|

Structure-specific model of hemoglobin cooperativity.

Abstract: A generalization of the Szabo-Karplus statistical mechanical model for hemoglobin cooperativity is formulated. The model fits the available thermodynamic and spectroscopic data with assumptions that are consistent with structural results and empirical energy function calculations. It provides a mechanism of hemoglobin cooperativity that is a generalization of the proposals of Monod, Wyman, and Changeux and of Perutz. The role of nonsalt-bridge related sources of constraints on ligand affinity and the mode of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…For the pH-dependency studies, species 11,21, and 32 were studied as hybrids (AB) in mixture with the two parent tetramers, AA and BB, according to Scheme I. The parent tetramers for species 11 are species 01 and 23; for species 21 they are species 01 and 41; for species 32 they are species 23 and 41 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the pH-dependency studies, species 11,21, and 32 were studied as hybrids (AB) in mixture with the two parent tetramers, AA and BB, according to Scheme I. The parent tetramers for species 11 are species 01 and 23; for species 21 they are species 01 and 41; for species 32 they are species 23 and 41 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although numerous models have been proposed containing various mixtures of "concerted" (6) and "sequential" (7) processes (e.g., see refs. [8][9][10][11][12], further progress has awaited experimental resolution of the actual energetics of cooperativity for the 10 microstates of ligation. The recently resolved distributions (13)(14)(15) and related findings (16,17) provide a necessary information base for deducing the rules that connect tertiary and quaternary switching with hemoglobin cooperativity.…”
mentioning
confidence: 99%
“…The SK model was generalized and revised later by Lee and Karplus (SKL) (21,22), motivated by two results. First, X-ray crystallography of the mutant hemoglobin Kansas showed that the salt bridges do not break in the crystal upon CO binding to the T quaternary structure, in sharp contrast to the prediction of the Perutz mechanism.…”
Section: The Generalized Szabo-karplus Model Of Lee and Karplusmentioning
confidence: 99%
“…4) stretches by 0.9 Å upon oxygenation of the T quaternary structure in the crystal (15). 2 The relative thermodynamic weights for a single subunit of the 4 possible species of the T quaternary structure in the SKL model at neutral pH are (21,22): 1 þ mH/S þ Kr 2 p þ KrpmH/S, where m is the concentration of hydroxyl ions and H is the hydroxyl ion binding constant to the broken salt bridge. The second and fourth terms correspond to the weights of subunits with broken and neutralized salt bridges (inter-subunit in the case of a subunits and intra-subunit in the case of b subunits), and the first and third terms are the same as in the partition function at alkaline pH of equation (7).…”
Section: Notesmentioning
confidence: 99%
“…Furthermore, CO binding to the reassembled recombinant deoxy tetramer was found to be monophasic under all conditions. Hb has long been studied as a model compound for many biochemical phenomena and continues to be the object of intense work to elucidate the molecular details of protein-protein recognition, allosteric regulation, ligand binding and dynamics, spectroscopy, energetics of cooperativity, and structure-function relationships (1)(2)(3). X-ray structures of liganded (R), unliganded (T) states, and with several intermediate species have been solved to high resolution and have provided much information on the detailed characterization of the mechanism of action by Hb (4 -7).…”
mentioning
confidence: 99%